PENGARUH UKURAN KAP, OPINI AUDITOR, FEE AUDIT, UKURAN PERUSAHAAN, PERGANTIAN MANAJEMEN, DAN KESULITAN KEUANGAN TERHADAP AUDITOR SWITCHING - Tara Anisa, 13.05.52.0166; Alfasadun, Alfasadun (Students' Journal of Accounting and Banking, 2017)
This research examined the effect of accounting firm size, audit opinion, audit fee, firm size, turnover management, and financial distress of the auditor switching. This research was conducted at the Indonesian Stock Exchange by using analysis unit manufacturing companies that have gone public. The sampling method in this research using purposive sampling the study period of 2014 to 2016. The relationship and or influence between independent variables and the dependent variable is explained by using logistic regression analysis. The results of the study are as follows: firm size influence the auditor switching, whereas the accounting firm size, audit opinion, audit fee, turn over management, and financial distressdoes not influence the auditor switching.Keywords: accounting firm size, audit opinion, audit fee, firm size, turnover management, financial distress, auditor switching